Interventions to Enhance Rational Drug Use, Awareness, and Self-Efficacy in Medication Adherence Among Older Adults: An Experimental Study - Türkan Akyol Güner (Yaşlı Sorunları Araştırma Dergisi, 2025)
The aim of this study was to evaluate the effects of interventions applied to improve rational drug use, awareness, and medication adherence self-efficacy in older adults. The study was conducted with 68 older adults who met the inclusion criteria. In the study, 55.9% of the intervention group and 58.9% of the control group were male. The average age of the intervention group was 70.32±5.60, and the average age of the control group was 71.20±5.41. It was determined that, following the inter-ventions applied to older adults in the intervention group, the mean scores of the Rational Drug Use Scale (RDUS), Rational Drug Use Awareness Scale (RDUAS), Medication Adherence Self-Efficacy Scale – Short Form (MASES-SF), and the WHO (5) Well-being Scale increased significantly compared to the control group (p<0.05). Interventions to improve rational drug use, awareness, and self-efficacy in medication adherence positively impacted older adults' knowledge, treatment adherence, and overall well-being.